Combined modelling and experimental studies of failure in thick laminates under out-of-plane shear. (15th November 2016) - Jia, L.; Yu, L.; Zhang, K.; Li, M.; Jia, Y.; Blackman, B.R.K.; Dear, J.P.
Abstract: A multi-scale model validated with out-of-plane shear testing is presented to analyse thick composite structural failure. Key features of this multi-scale analysis approach are inclusion of shear non linearity and modelling the response at a sub-laminate level whilst the structural failure is predicted at a ply level. Based on this multi-scale approach, a user-defined FORTRAN subroutine (VUMAT) has been written for ABAQUS/EXPLICIT solver and is used to model the shear nonlinearity and intra-laminar failure. In addition, a cohesive zone model is used to predict the inter-laminar delamination. The modelling has been employed to predict the failure processes for Iosipescu shear test specimens with different fibre orientations. The results show that both the failure mode and the load-displacement trace for finite element simulations agree closely with the experimental findings. This demonstrates the validity of this multi-scale, nonlinear, three-dimensional model for thick laminates. In particular, for the Iosepescu shear test, the effect of the fibres being aligned along the length of the specimen or out-of-plane is investigated as well as different dimensions of the specimen. These simulations are validated by experiments using Digital Image Correlation (DIC).